Social Rehabilitation for Vagrants and Beggars Through Institutional Approach in Indonesia - Yanuar Farida Wismayanti; Husmiati Yusuf; Alit Kurniasari; Aulia Rahman; Mery Ganti; Widiarto Widiarto; Hari Harjanto Setiawan; Badrun Susantyo; Ita Konita; Delfirman Delfirman; Muhammad Belanawane (Asian Social Work Journal, 2021)
The problem of vagrants and beggars is a fairly complex issue in big cities such as Jakarta, Bandung, Semarang, Surabaya, Medan, and Makassar. These big cities' charms have attracted the poor with low education levels and limited access to education, health, and skill development. Many service programs for the vagrants and beggars have been carried out, yet the problems related to the vagrants and beggars have never subsided. Quantitative and qualitative approach are used to determine how the condition of social rehabilitation services carried out for vagrants and beggars by the government and the community, the extent of their level of social functioning, and the role of social workers in social rehabilitation services. A population sample is a group of homeless people and beggars who receive social services in government institutions and community organisation. The sampling used was the purposive sampling method with a sample of 487 respondents in the six provinces, namely DKI Jakarta, West Java, East Java, Central Java, North Sumatra, and South Sulawesi. This research found that in the process of social rehabilitation services for vagrants and beggars, there are still differences in the service standards between institutions; limitations in human resources, including social workers; limited budget support; limited cooperation, and coordination between local government organizations at the provincial, regency/municipal, and central government along with related stakeholders. It conclude that the national policy platform related to the handling of vagrants and beggars needs to be the focus to overcome the complexity of the problems faced by this marginal group.